Triple sexually transmitted infections among pregnant woman in the context of Elimination of mother to child transmission in Southern Ethiopia: Reports from a survey of questionnaires and laboratory studies. - Israel, Eskinder; Hizkel, Iskindir; Geta, Temesgen; Feleke, Tihun; Samuel, Beniyam; Markos, Desta (Frontiers in Global Women's Health, 2023)
Introduction Sexually transmitted infections (STIs) cause a wide range of public health problems if left untreated. They can lead to adverse birth outcomes, including stillbirth, fetal loss, neonatal death, preterm birth, and low birth weight. Although great efforts have been made to reduce STIs nationally, their incidence remains high in Ethiopia, and their co-infection calls for urgent action. Therefore, this study aimed to identify the determinants of three STIs among pregnant women attending antenatal care (ANC) in the context of the elimination of mother-to-child transmission in public health facilities in Sawla Town, Gofa zone, Southern Ethiopia. Methods A cross-sectional study design was conducted among pregnant women attending antenatal care in public health facilities in Sawla Town, Southern Ethiopia, from May to July 2022. Data were collected from pregnant women’s serum using an HIV rapid test, an HBsAg rapid test device, and a VDRL for HIV, HBV, and syphilis, respectively. Descriptive statistics, such as frequencies and percentages, were used to describe each relevant variable. Logistic regression analyses were used to identify the determinants of STIs. Results A total of 484 pregnant women attending antenatal care were screened. The mean age of the women was 24.0 ± 4.6 years, and nearly half of the participants had completed secondary school or higher. The overall seroprevalence of three STIs (HIV, HBV, and syphilis) among pregnant women was 6.8%. These three sexually transmitted infections were shown to be more common among pregnant women who were not able to read and write, had tattoos, had previously had an abortion, and had a history of multiple sexual partners. Conclusions The seroprevalence found in this study was intermediate in comparison with the WHO standard. Efforts should be made to strengthen the existing health education and RH service integration on STI screening, and treatment that further eliminates vertical infection.